Depois da cidade colonial e imperial - que cidade construímos ?: estudo de caso : SJDR no século XX - Ana Elisa de Resende Raposo (2010)
The Houses of Chamber in Minas during of XVIII and XIX centuries had a structure paper of the politic-administrative from that time. The mental universe based in the ideals of Decorum helped to conform and to consolidate the Urban Landscape of the cities of Minas Gerais. Throughout of bibliographic review about the urbanization in Brazil and Minas Gerais stayed the mystifying the notion of lack of urban plane as in Minas as in the rest of the Colony. To Roberta Delson, with the golden discovers in the inland of the colony were developed the Director Planes to the dominium of the territory of the ideal of order and regularity, as the form of the representation of the colonial authority. In Minas case, the organically and irregularities of the occupation were confused with the lack of plane, principal if compared with a kind of occupation of Spanish America (regular and quadrangle). Bastos and Borregos works came to break the myth of this notion. At character more spontaneous of the firsts occupations of run of the gold, overload the occupation ruled in the Decorum ideal of the settlement and structures by the Houses of Chamber and Jail. The urban facetious of this planed cities at light of Decorum were led and recognized as bulwark of genuine Brazilian art. As it was a transposition of the concept to the XX century? Which was the paper of the public power in the construction of the urban space in the XX century? To answer these questions, I propose the study of SJDR-MG case. The city is the donating of the historic heap, cultural and environmental built along of the XVIII, XIX and beginning of the XX centuries. In contraposition to the Decorum of the present settlement in the XVIII and XIX centuries, urban renovations and urban expansions without any control market the city in the XX century. The urban transformations of the second half of the XX century, the urban dense, the economic and social press, the lack of effective public politics over the space, indelible transformed the conjoin of the landscape recognized to federal protection in 1938 and the same conjoin delineated in 1947. Only at the end of the decade of 1990 that the Urban Environment Heritage of SJDR was recognized in his totally by the public power, with the creation of the CMPPC (Conselho Municipal de Preservação do Patrimônio Cultural) and the delineated of the protected area of the municipality urban architectonic conjoin, by the Law 3531, 2000. Unhappy the result of the city from the XX century, its not that ideal ruled in the perfection, harmony, beauty and hygiene from the before centuries, by the contrary very much. One of the justificative to the phenomenon was the form of the public power a long of the XX century that greatly reduced the ideal influence of the Decorum of the settlement. To illustrated better this affirmation, was realized a study of the laws, resolutions and decrees from 1900 to 2000, to understand the means of actuation of the public power and how they reflected on the urban space. Finally, the landscape from the XX century built at the city of SJDR, aggregated to the landscape of the XVVIII and XIX centuries expresses unsustainable, complex and dichotomy. One of the proposes of the Direct Plane of 2006 is to try to work the degradation of the areas in a participant and sustainable way, once there is in this beginning of century great preoccupation with the preservation of the Urban Environmental Heritage remaining and with the building of a new city more equilibrated and harmony.